Some considerations with regard to the surgical treatment of vulvar cancer - Bedoya Hevia, Mariano (2015)
Dissemination and knowledge of vulvar cancer is paramount. Although it is a rare and poorly understood condition, his interest is in making a timely diagnosis, followed by an enlarged super extended as surgery or cancer surgery is conceived at present. This surgery offers huge possibilities of healing as the primary lesion remains stationary, although, it is true, that gives metastases with great frequency, as indicated Taussig observing up to 66% of them in the regional lymph not spread to distant organs, comments they are confirmed by Way and other researchers.